The inevitability of arbuscular mycorrhiza for sustainability in organic agriculture—A critical review - George, Nirmal Philip; Ray, Joseph George (Frontiers in Sustainable Food Systems, 2023)
The arbuscular mycorrhizal fungi (AMF) are significant fertility-promoting microbes in soils. They enable soil fertility, soil-health and boost crop productivity. There are generalist and specialist groups among AMF in natural soils. Optimized use of specific AMF concerning crops and soils can improve agricultural sustainability. Thus, AMF is becoming an inevitable biological tool for improving crop productivity and soil health. Especially in the context of chemicalized agriculture undermining the sustainability of food security, safety, and human and ecosystem health, alternative agricultural means have become inevitable. Therefore, AMF has become essential in nature-friendly, organic agriculture. Of such farm fields, natural biological activity is enhanced to sustain soil fertility. Crops show increased innate immunity against pests and diseases in many such systems. Moreover, ecosystems remain healthy, and the soil is teeming with life in such farms. The primary goal of the review was a thorough critical analysis of the literature on AMF in organic agriculture to assess its efficiency as an ecotechnological tool in sustainable agricultural productivity. The novelty is that this is the first comprehensive review of literature on AMF concerning all aspects of organic agriculture. A vital systematic approach to the exhaustive literature collected using regular databases on the theme is followed for synthesizing the review. The review revealed the essentiality of utilizing specific mycorrhizal species, individually or in consortia, in diverse environmental settings to ensure sustainable organic crop production. However, for the exact usage of specific AMF in sustainable organic agriculture, extensive exploration of them in traditional pockets of specific crop cultivations of both chemical and organic fields and wild environments is required. Moreover, intensive experimentations are also necessary to assess them individually, in combinations, and associated with diverse beneficial soil bacteria.